Infant Botulism and Honey: ENY-128/AA142, rev. 10/2009 - Sanford, Malcolm T.; Atkinson, Eddie; Ellis, Jamie (EDIS, 2009)
Revised! ENY128, a 2-page fact sheet by Malcolm T. Sanford, Eddie Atkinson, and Jamie Ellis, prepares beekeepers to answer questions responsibly about honey as a potential source of C. botulinum spores, which can cause botulism in infants under 12 months of age. Includes references. Published by the UF Department of Entomology and Nematology, October 2009. ENY-128/AA142: Infant Botulism and Honey (ufl.edu)